2006
DOI: 10.4012/dmj.25.138
|View full text |Cite
|
Sign up to set email alerts
|

Development of .BETA.-tricalcium Phosphate/Collagen Sponge Composite for Bone Regeneration

Abstract: Synthetic biomaterials have been developed and used for bone grafting. Here, we developed a biodegradable sponge composite for bone tissue engineering by combining β-tricalcium phosphate(β -TCP)and collagen. In addition, we sought to determine the optimal β-TCP granules/collagen ratio by evaluating and bone formation in vivo. Porous β-TCP granules were mixed with atelocollagen hydrochloride solution at various ratios -0.02, 0.05, 0.1, and 0.2 g/mL. The resultant mixtures were freeze-dried and subjected to dehy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
50
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(58 citation statements)
references
References 27 publications
1
50
0
1
Order By: Relevance
“…Collagen is known to be a promising material for transplantation, owing to its diverse applications in tissue engineering and its excellent biocompatibility and biodegradability 3) . It is possible to easily form a collagen gel that can be either injected or implanted into the defect site.…”
Section: Introductionmentioning
confidence: 99%
“…Collagen is known to be a promising material for transplantation, owing to its diverse applications in tissue engineering and its excellent biocompatibility and biodegradability 3) . It is possible to easily form a collagen gel that can be either injected or implanted into the defect site.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that -TCP has good biodegradability and osteoconductivity as a scaffold material for bone tissue engineering (Le geros, 2002;Matsuno et al, 2006). With regard to shape availability, both block and granular forms are available.…”
Section: β-Tcp Beadsmentioning
confidence: 99%
“…Osteoblast-lineage cells or bone marrowderived host cells are commonly used for this purpose, and such cells are harvested, cultured in vitro, and then inoculated into scaffolds composed of poly-L-lactic acid (PLLA) 1) , poly (DL-lactic acid-co-glycolic acid) (PLGA) [2][3][4][5] , or collagen gel [6][7][8] . Scaffolds with osteogenic cells are then implanted into the host body to induce new bone formation 9,10) .…”
Section: Introductionmentioning
confidence: 99%